2021
DOI: 10.1021/acs.est.0c08563
|View full text |Cite
|
Sign up to set email alerts
|

Individual Prey Specialization Drives PCBs in Icelandic Killer Whales

Abstract: Interindividual variation in prey specialization is an essential yet overlooked aspect of wildlife feeding ecology, especially as it relates to intrapopulation variation in exposure to toxic contaminants. Here, we assessed blubber concentrations of an extensive suite of persistent organic pollutants in Icelandic killer whales (Orcinus orca). Polychlorinated biphenyl (PCB) concentrations in blubber were >300-fold higher in the most contaminated individual relative to the least contaminated, ranging from 1.3 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…Previous studies suggested that some populations of North Atlantic killer whales are strongly associated with mackerel stocks 7 . Since killer whales are opportunistic hunters capable of switching prey 6 , one could easily imagine killer whales in Greenland having a mixed diet of both mackerel and seal species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that some populations of North Atlantic killer whales are strongly associated with mackerel stocks 7 . Since killer whales are opportunistic hunters capable of switching prey 6 , one could easily imagine killer whales in Greenland having a mixed diet of both mackerel and seal species.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, stomach contents and fecal samples are both challenging to obtain, only represent recent feeding patterns and, in the case of stomach contents, can only be obtained from deceased individuals that may not represent the healthy part of the populations 4 . Thus, the use of chemical tracers measured largely from biopsies collected remotely from cetaceans has increased in recent decades due to relative ease of sampling and ability to reflect integrated diet signals over time 5 , 6 . Stable isotopes of carbon and nitrogen in the skin have revealed some inter and intra-population variation in the feeding patterns of cetaceans, providing diet composition estimates mostly at the trophic level, although species-level precision from stable isotopes remains challenging 7 9 .…”
Section: Introductionmentioning
confidence: 99%
“…As the top predators in the PRE, dietary uptake of humpback dolphins is the main route for the accumulation of contaminants. Thus, altered prey consumption imposes potential influences on their contaminant exposures. For the PRE humpback dolphins, a demographic study indicated a reduction of around 2.5% in population size per year . Contaminant exposure was reported to be highly associated with population decline via compromising the immune functions and reproduction. , However, the load of endocrine-disrupting chemicals in response to altered prey consumption patterns in humpback dolphins has not been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…than the levels in Norwegian fish-eating killer whales (429 mg/kg l.b. ), hundred-fold lower than mixed-diet killer whales (Remili et al, 2021), and well below the lowest value (9.0 mg/kg l.b.) proposed as the toxicity threshold concentration for the onset of physiologic effects in marine mammals (Kannan et al, 2000;Jepson et al, 2016).…”
Section: Statistical Analysis Of Persistent Organic Pollutants and Mo...mentioning
confidence: 69%
“…Generally, POPs experience biomagnification within food webs since dietary intake acts as the main route for contaminant accumulation. Thus, high levels of POPs have been documented in killer whales from different geographical areas (mostly from the northern hemisphere; Desforges et al, 2018;Andvik et al, 2020;Lawson et al, 2020;Remili et al, 2021). Substantial differences due to their ecotype (based on prey specialization) influence the accumulation of contaminants in killer whales, which may exert different effects on different populations worldwide (Desforges et al, 2018).…”
Section: Introductionmentioning
confidence: 99%